SYARAT PRESTASI YANG LUAR BIASA DALAM PEMBERIAN KEWARGANEGARAAN KEPADA ORANG ASING MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN REPUBLIK INDONESIA - Kadek Tegar Wacika; Ni Nengah Adiyaryani (Kertha Negara : Journal Ilmu Hukum, 2015)
In terms of granting the status of Indonesian Citizenship by the state to Foreign Citizens, the state has several considerations. The raised issue is “The Requirement of Exceptional Achievement in Terms of Granting Citizenship to Foreigners According to the Law No. 12 for the Year 2006 Concerning the Citizenship of the Republic of Indonesia”. The research method used in this journal is normative juridical, which is through the legal and literature approach. When look at the explaination of Article 20 of Law No. 12 for the Year 2006, foreign citizens who will acquire the status of Indonesian Citizenship must fulfill the four essential elements, which are; the element of foreigner, the element of contribution to the state, the element of exceptional2achievement and the element of state’s interests. The meaning of exceptional achievement is the real work that is accomplished by the foreigner who will be granted the status of Indonesian Citizenship and the work receives its recognition from the Indonesian Government.